The Prospects and The Competitiveness of Textile Commodities and Indonesian Textile Product in the Global Market - Dwi Prasetyani; Ali Zainal Abidin; Nanda Adhi Purusa; Fahrein All Sandra (Faculty of Economic and Business, 2020)
This study has two objectives: first, to test the competitiveness of Textile Commodities and Indonesian Textile Product (TPT) in the global market and identify the prospects of the new export markets. Second, identify the competitiveness of the textile industry using case studies in the Solo Raya region. The Revealed Comparative Advantage (RCA) and Export Product Dynamics (EPD) methods are using in this study. The results show that Indonesian TPT commodities have a lost opportunity category in the central export destinations countries, such as a decline in market share. Indonesian TPT commodities have prospects in Austria, Canada, Finland, Norway, Portugal, Qatar, and Sweden due to competitiveness and domination in the market. Besides, the condition of the Indonesian textile industry competitiveness shows low competitiveness in terms of factor conditions, demand conditions, supporting and related industries, strategy, structure, and competition that are components of Porter's diamond model.JEL Classification: L6, L67How to Cite:Prasetyani, D., Abidin, A. Z., Purusa, N. A., & Sandra, F. A. (2020). The Prospects and The Competitiveness of Textile Commodities and Indonesian Textile Product in the Global Market. Etikonomi: Jurnal Ekonomi, 19(1), 1 – 18. https://doi.org/10.15408/etk.v19i1.12886.